Evaluation of pentoxifylline and Basal Medium Eagle supplemented to diluent on cryopreserved goat spermatozoa. Issue 10 (28th July 2020) - Nazari, Parisa; Farshad, Abbas; Vaziry, Asaad; Rostamzadeh, Jalal
Abstract: This study investigated the effect of pentoxifylline (PTX) and Basal Medium Eagle (BME) on frozen–thawed goat spermatozoa. Immediately after initial examination of ejaculated semen, samples were pooled and reexamined for quality. Then, samples were divided into eight equal aliquots and diluted with a basic tris‐extender containing PTX (3, 6, 9 mM) and BME (5 mM) to reach a final concentration of 25 × 10 9 and frozen. After 24 hr, the samples were individually thawed at 37°C for 30 s and evaluated for different characteristics. Obtained post‐thaw results from Computer‐Assisted Sperm Analysis indicate using of 3 and 6 mM PTX led significantly to an improvement in total motility, progressive motility and velocity characteristics of spermatozoa, except the beat/cross frequency (BCF) which indicated statistically no differences ( p > .05) among control and treatments. Diluents prepared with BME (5 mM) and PTX alone (3 and 6 mM) improved significantly the membrane integrity–functionality, acrosome integrity and also hyaluronidase activity. Regarding recovery rate, the results showed significantly ( p < .05) higher values for diluents containing 3 and 6 mM PTX compared to other groups. Malondialdehyde concentration exhibited also a significant difference ( p < .05) in diluents supplemented with 5 mM BME, 3, 6 and 9 mM PTX, and mixture of 3 mM PTX and 5 mM BME which illustrate a similarity for active mitochondria, apoptotic‐like and dead spermatozoa. Finally, the ratio of sperm chromatin dispersion stained spermatozoa presented significant differences ( p < .05) among treatments in which the diluents added PTX alone demonstrated significantly lower values than control and extenders containing the mixtures of BME and PTX. In conclusion, the observation in this study indicates using of 3 and 6 mM PTX and BME alone may improve significantly ( p < .05) the quality of cryopreserved goat spermatozoa.